The formation of saline lands and methods of salt washing of saline lands - Djapakov Norboy Boriboevich.; Djapakov Norboy Boriboevich. (Zien Journals, 2022)
In this article, we talked about the methods of washing soil salts, taking into account that the demand for fertile soils has increased due to the increased salinity of the soil, and many fertile lands are becoming unusable due to salinity.
Keywords: gradual process; ecological problem; ecological crisis; soil compaction